Semiotic Approach to Visual Representation of Islamic Values in Islamic Early Childhood Education Instagram Content - Annisa Bela Pertiwi; Budiman Budiman (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines visual communication strategies on the Instagram accounts of two Islamic Early Childhood Education (ECE) institutions in Bandung, TK Islam Taman Firdaus and Rumah Bintang Islamic Preschool, in building public image and trust in the digital era. A descriptive qualitative approach is employed, supported by quantitative data collected through content observation, interviews with media managers, and questionnaires administered to 20 parents of prospective students. The analysis draws on Roland Barthes’ visual semiotics and digital marketing communication theory to interpret symbolic meanings and assess visual effectiveness. The results show two equally effective visual communication patterns with different orientations. These differences are influenced by communication strategies, particularly a multichannel approach that emphasizes professionalism and visual consistency through structured layouts, sans-serif typography, and color compositions such as yellow, orange, blue, and white. The mean perception score was 3.66, while the highest scores were regarding visual appeal (43) and message clarity (42). Rumah Bintang Islamic Preschool, on the other hand, emphasizes emotional intimacy and spiritual values through blue-orange tones and narrative-based visuals, achieving a mean score of 3.9. The highest scores were found in visual consistency (43) and the representation of Islamic values (45). Both approaches show that the effectiveness of visual communication does not rely on a particular visual style, but rather on the consistency between visual elements and narrative messages to their audience's expectations and institutional values. When aligned with institutional goals and audience engagement, different visual strategies can achieve similar levels of effectiveness. Practically, this study offers guidance for Islamic ECE institutions in designing digital visual communication strategies by ensuring coherence between visual consistency, narrative content, and platform usage in line with their communication objectives.